Marginalized Women in the Political Agenda of North Sumatra: Aspirations for welfare and Legal Protection - Detania Sukarja; Harmona Daulay; Mahmul Siregar; Devi Yulida; Annisa Hafizhah (Mahadi: Indonesia Journal of Law, 2026)
This study examines the extent to which gubernatorial candidates in North Sumatra incorporate women’s rights and welfare into their policy agendas, with specific attention to marginalized women. Although the 1945 Constitution of the Republic of Indonesia mandates the state to safeguard the welfare of all citizens, many women in marginalized positions continue to experience limited access to education, healthcare, economic opportunities, and legal protection. Using a qualitative research design, this study draws on in-depth interviews with 12 marginalized women in Medan, including domestic workers, small-scale traders, women with disabilities, and housewives from economically disadvantaged households. The research explores women’s expectations regarding gubernatorial policies that could improve their access to welfare services, education, healthcare, and legal safeguards. The findings indicate that patriarchal social structures, unequal access to public services, and ongoing gender-based violence remain dominant challenges for marginalized women in North Sumatra. Despite gradual improvements in gender equality, substantial disparities persist. While the policy platform of the gubernatorial candidate pair Muhammad Bobby Afif Nasution and Surya identifies women’s empowerment as a strategic priority, the proposed initiatives lack clear operational frameworks. Conversely, the policy agenda of Edy Rahmayadi and Hasan Basri Sagala places limited emphasis on gender-related concerns. Marginalized women express a strong demand for policies that support skills development, access to micro-capital, and more effective legal protection, accompanied by transparent and accountable governance. This study highlights the need for more concrete and inclusive policy commitments to ensure that women’s empowerment becomes an integral component of regional development in North Sumatra.